Korea the first war we lost - Alexander, Bevin (Hippocrene, 2004)
This book is an effort to demonstate that Western leaders, especially those from United States, received ample signals that, had the leaders responded to them, could have prevented the entry of Red China into the war and, even after Communist China did enter, could have ended the war much sooner and at much less cost. -- preface